Solitary Plasmacytoma of The thumb: Arare Case Report - Alireza Pahlevansabagh; Dawood Jafari; Hamid Taheri; Hooman Shariatzadeh; Farid Najd Mazhar (Medical Journal of The Islamic Republic of Iran, 2009)
A solitary plasmacytoma of bone occurs in approximately 2-5% of patients with myeloma.The lesion mostly found in the axial skeleton and have infrequently been reported to arise in the hand,and usually occur in the distal phalanges.We report the interesting case of a 75-year-old man who developed a solitary lytic lesion of the thumb proximal phalanx.This lesion was explored through MR imaging and histologic examination,and then a final diagnosis of plasmacytoma was determined.He was treated with fractionated radiotherapy and no complication was detected with this procedure.The clinical, imaging, and histologic findings of this case are presented here.